Faktor-Faktor Yang Mempengaruhi Praktik Perataan Laba Pada Perusahaan Manufaktur - Chyntia Natalia, Liana Susanto (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence the influence of profitability, financial leverage, institutional ownership, and firm size towards income smoothing practice in manufacturing companies listed in Indonesia Stock Exchange from period 2015 – 2017. This research used purposive sampling method with total sampel 60 manufacturing companies that have been selected with certain criteria. The data used secondary data in the form of financial statements. This research used logistic regression analysis with Statistical Product and Service Solution (SPSS) software to process the data. The result of research shows that profitability has negative significant influence towards income smoothing practice, and financial leverage, institutional ownership, and firm size have no significant influence to towards income smoothing practice